School Bullying and Empathy among Preadolescents: A Correlational Study - Najia Zulfiqar, Asma Bibi, Somayia Hafeez (PJE, 2023)
The present study aimed to examine the relationship between school bullying and empathy among preadolescents. Bullying was studied across three dimensions of being a bully, victim, and fighting, whereas empathy was examined as a unidimensional construct. Data were collected from preadolescents between ages 10-12 years in District Haripur. Descriptive statistics, frequencies/percentages, correlation, and t-tests were performed. The findings showed that there is a negative relationship between school bullying and empathy, and less empathic preadolescents were more tended to bully and fight more than more empathic. An equal number of participants reported fighting with others and bullying them in one last month. However, a large majority reported being the victims of bullying 7 or more times in the last 30 days (52, 36.4%). The level of empathy was in the moderate to high range among 178 students and low among 22 students. Boys scored higher on all dimensions of bullying and were less empathic than girls. These findings highlight the need for the screening, prevention, and intervention of school bullying. Can help teachers, parents, school administrators, and counselors to eradicate aggressive behavior.